Pengembangan Model Pembelajaran Alternasi untuk Meningkatkan Written Communication dan Compassion Skills Calon Guru IPA - Aris Singgih Budiarso (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This research aims to obtain an alternation learning model that is valid, practical, and effective to improve Written Communication Skills (WCS) and Compassion Skills (CS) of pre-service science teachers. This learning model is urgent to develop, considering that WCS and CS are very important for pre-service science teachers, and from the results of empirical studies, there is still no learning model specifically used to improve WCS and CS. This research is a development research with a design adapted from educational design research with stages: introduction, prototyping, and final. The results of prototyping in the form of alternation learning models and their devices were carried out on a limited-scale test in the basic physics II course involving 30 pre-service science teachers. In comparison, the wide-scale test involved 90 pre-service science teachers from 3 three different universities using a one-group pretest-posttest design. This study used data collection methods including: interview, observation, FGD, test, questionnaire, and documentation. Validity data was analyzed using Aiken's V formula and inter-rater reliability calculation using Kendall's W. Practicality data was analyzed using categorization and inter-rater reliability calculation using Weighted Kappa. Effectiveness data were analyzed using the Wilcoxon signed-rank test. The research findings showed that: (1) validity, the alternation learning model fulfills the element of novelty (content validity) and between the elements of the model has consistency and is developed based on learning theory (construct validity); (2) validity, the alternation learning model device has high validity and moderate and substantial reliability; (3) practicality, the alternation learning model is practical when implemented in learning with a good category with good and very good inter-rater reliability intervals; and (4) effectiveness, there is a significant increase with a very large effect size on WCS and CS after pre-service science teachers following the implementation of the alternation learning model. Based on the research findings, it can be concluded that the alternation learning model meets the valid, practical, and effective criteria, so it is feasible to use to improve WCS and CS of pre-service science teachers.
Entry oleh Arif 2026 Maret 16
Keywords: Alternation Learning Model; Written Communication Skills; Compassion Skills